1993
DOI: 10.1152/jn.1993.69.5.1465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vasoactive intestinal polypeptide on the response properties of cells in area 17 of the cat visual cortex

Abstract: 1. Vasoactive intestinal polypeptide (VIP) was iontophoretically applied to a population of 90 single cells in the primary visual cortex (area 17) of the cat. Response magnitude, response selectivity, spontaneous activity, and the ratio between the visual response and spontaneous activity (signal-to-noise ratio) of the cells were assessed quantitatively before and during drug application. 2. VIP had little effect in the absence of visual stimulation, with only 29/90 (32%) of the cells showing a change of even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…VIP is present in many GABAergic neurons, and is thought to be co-released with GABA during interneuron activation. It has been shown that VIP can exert substantial changes in activity of V1 neurons in the cat [62], with effects depending on cortical layer. Thus, in addition to being useful for labeling a specific kind of GABAergic interneuron, VIP can also act as a neurotransmitter in V1 and modify cortical computations.…”
Section: Discussionmentioning
confidence: 99%
“…VIP is present in many GABAergic neurons, and is thought to be co-released with GABA during interneuron activation. It has been shown that VIP can exert substantial changes in activity of V1 neurons in the cat [62], with effects depending on cortical layer. Thus, in addition to being useful for labeling a specific kind of GABAergic interneuron, VIP can also act as a neurotransmitter in V1 and modify cortical computations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance in the cat visual cortex, exogenously applied VIP had little or no effect on recorded neurons in the absence of visual stimulation, but enhanced their visual responses (Murphy et al, 1993; Fu et al, 2014). Consistently, by activating VPAC1 receptors and cAMP/PKA signaling, VIP reduced the slow AHP current and the tonic potassium current which regulates the excitability of hippocampal and cortical pyramidal neurons (Haug and Storm, 2000; Hu et al, 2011).…”
Section: Targets and Functionsmentioning
confidence: 99%
“…Although neurophysiological studies regarding the actions of VIP are few, this peptide has been found to produce a number of different actions within the CNS. VIP has been found to depolarize brain stem neurons and increase the excitability of hippocampal and neocortical neurons (Haas and Gahwiler 1992;Kohlmeier and Reiner 1999;Murphy et al 1993;Pawelzik et al 1992). This peptide has also been shown to enhance GABAergic synaptic transmission in cultured hippocampal neurons presumably through a presynaptic site of action (Wang et al 1997).…”
Section: Vip Depolarizes Relay Neurons In Vb By Enhancing I Hmentioning
confidence: 99%
“…VIP is also widely distributed throughout the central and peripheral nervous system where it may serve as a putative neuromodulator (Gozes and Brenneman 1989). VIP has been found to produce a variety of actions including alterations in intrinsic properties of neurons or synaptic transmission in the CNS (Gozes and Brenneman 1989;Kohlmeier and Reiner 1999;Murphy et al 1993;Wang et al 1997). This peptide has been localized within TRN neurons (Burgunder et al 1999b), and VIP receptors are distributed within primary relay thalamic nuclei such as VB and the dorsal lateral geniculate nucleus (Sheward et al 1995;Usdin et al 1994;Vertongen et al 1997).…”
Section: Introductionmentioning
confidence: 99%